2019
DOI: 10.1002/smll.201804565
|View full text |Cite
|
Sign up to set email alerts
|

Black Phosphorus, a Rising Star 2D Nanomaterial in the Post‐Graphene Era: Synthesis, Properties, Modifications, and Photocatalysis Applications

Abstract: Semiconductor photocatalysis, a sustainable and renewable technology, is deemed to be a new path to resolve environmental pollution and energy shortage. The development of effective photocatalysts, especially the metal‐free photocatalysts, is a critical determinant of this technique. The recently emerged 2D material of black phosphorus with distinctive properties of tunable direct bandgap, ultrahigh charge mobility, fortified optical absorption, large specific surface area, and anisotropic structure has captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
169
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(176 citation statements)
references
References 238 publications
0
169
1
Order By: Relevance
“…Transition metal dichalcogenides (TMDCs) are a family of 2DLMs in the form of MX 2 compounds, where M is a transition metal (Mo, W, Re) and X is a chalcogen (S, Se, Te). TMDCs are promising for electronic applications due to their semiconducting behaviour as opposed to semi-metallic graphene, and better thermal stability than materials such as black phosphorus and silicene [14][15][16][17][18][19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transition metal dichalcogenides (TMDCs) are a family of 2DLMs in the form of MX 2 compounds, where M is a transition metal (Mo, W, Re) and X is a chalcogen (S, Se, Te). TMDCs are promising for electronic applications due to their semiconducting behaviour as opposed to semi-metallic graphene, and better thermal stability than materials such as black phosphorus and silicene [14][15][16][17][18][19].…”
mentioning
confidence: 99%
“…Articles in the field of optoelectronics and photonics are roughly 10% of the total published articles. Black phosphorus has been wellstudied due to its interesting material properties, but its technological relevance is low due to lack of air-stability [15,16]. It is interesting to observe that the number of reports on heterostructure (HS) devices is larger than that for almost any single material.…”
mentioning
confidence: 99%
“…It is found that the valance band maximum (VBM) and conduction band maximum (CBM) shift away from each other on decreasing thickness of phosphorene from 5 to 1 L with a concomitant increase in the work function from 4.5 eV (5 L) to 5.16 eV (1 L) . The band structure of phosphorene near VBM and CBM is mainly contributed by p z , unlike graphene whose VB and CB are fully contributed by p y orbital . Depending on the methods, the calculated bandgaps vary in the 0.10–0.36 eV range for bulk BP and 1.0–2.0 eV for mono‐layer phosphorene .…”
Section: Synthesis Structure and Propertymentioning
confidence: 97%
“…The band structure of phosphorene near VBM and CBM is mainly contributed by p z , unlike graphene whose VB and CB are fully contributed by p y orbital . Depending on the methods, the calculated bandgaps vary in the 0.10–0.36 eV range for bulk BP and 1.0–2.0 eV for mono‐layer phosphorene . In the same way, the experimentally measured bandgaps depend on the method of preparation and measurements (Table ).…”
Section: Synthesis Structure and Propertymentioning
confidence: 99%
“…It mainly exists in four allotropes, including white phosphorus (WP), red phosphorus (RP), violet phosphorus (VP), and black phosphorus (BP). Compared to the flammable WP as well as to poorly conductive RP and VP, BP with layered structure is the most thermodynamically stable one, featuring high conductivity, tunable direct bandgap, and anisotropic properties . In particular, the successful exfoliation of bulk BP into phosphorene through mechanical method or liquid‐phase sonication additionally brings out more exposed active sites and shortened ions pathways in comparison with the bulk counterpart .…”
Section: Introductionmentioning
confidence: 99%